Accumulated Strain, Negative Emotions, and Crime: A Test of General Strain Theory in Russia. (September 2013) - Botchkovar, Ekaterina; Broidy, Lisa
Drawing on a random sample of 340 adults, this study examines the relationships between strain, negative emotions, and criminal coping in the context of Russia. Extending the argument of general strain theory (GST), it also assesses the criminogenic potency of strain accumulation and raises the possibility that negative affect, accumulating from stressors closely grouped in time, heightens individual's sensitivity to concurrent or subsequent strains. Although the data suggest that the core variables of GST are operant in Russia, support for the theory is mixed. Strain appears to be generally associated with negative emotions, but negative emotions are not uniformly criminogenic. Negative emotions do not appear to mediate the association between strain and crime but moderate the strain–crime link and, in some cases, increase the enabling effects of strains on illegal coping. Overall, the findings suggest that negative affect likely produced by accumulation or clustering of negative events and conditions may heighten the crime-generating potency of other, less criminogenic strains.